The Effect of Teacher Skills and Availability of Learning Resources on Mathematics Problem Solving Skills at High Schools in West Java - Mayasari, Nanny; Nanang, Nanang; Nurhafsari, Asri; Asmara, Adi; Rohmah, Yuni Syifau (West Science Social and Humanities Studies, 2024)
This study investigates the influence of teacher ability and the availability of learning resources on mathematics problem-solving ability among high school students in West Java, Indonesia. Quantitative analysis was employed, utilizing survey questionnaires to gather data from a sample of 160 high school students. The study found significant positive relationships between teacher ability, learning resource availability, and mathematics problem-solving ability. Specifically, high-quality teaching and adequate provision of learning resources emerged as crucial factors contributing to students' problem-solving skills. The findings underscore the importance of investing in teacher training, professional development, and resource provisioning to enhance mathematics education outcomes in West Java.